PJMHS 2022
DOI: 10.53350/pjmhs22161882
|View full text |Cite
|
Sign up to set email alerts
|

Prevelance of Cervical Pain in Make-up Artist and Hair Dressers of Lahore

Abstract: Background: The overall incidence of cervical pain in makeup artists is well known. In our study we attempted to work on the prevalence of cervical pain among make-up artist and hair dressers due to prolong consecutive working hours and awkward body posture. Purpose: The sole purpose of this research was to find the prevalence of cervical pain among make-up artist and hair dressers while performing their make-up and hair cutting for consecutive long working hours. Method.It was a cross-sectional study design. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Furthermore, it was comparable to the study 17 which found that working more hours per week (46-59, as opposed to 8-39) was associated with a higher prevalence of neck pain. Another study 18 demonstrated neck pain and lack of movement in cervical muscles due to increased working hours and inappropriate posture, the results were comparable to the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, it was comparable to the study 17 which found that working more hours per week (46-59, as opposed to 8-39) was associated with a higher prevalence of neck pain. Another study 18 demonstrated neck pain and lack of movement in cervical muscles due to increased working hours and inappropriate posture, the results were comparable to the present study.…”
Section: Discussionsupporting
confidence: 90%